EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) DENGAN ASSESSMENT FOR LEARNING (AfL) PADA MATERI BANGUN RUANG DITINJAU DARI KEMAMPUAN SPASIAL SISWA KELAS VIII SMP NEGERI DI KABUPATEN KARANGANYAR - Pratiwi, Fitri Apriyani; Mardiyana, Mardiyana; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objective of this research was to investigate the effect of learning model toward learning achievement in mathematics viewed from the spatial ability. The learning models of this research were cooperative learning model of the TAI type with AfL, the cooperative learning model of the TAI type, and the direct learning model. This research used the quasi experimental research method with the factorial design of 3 x 3. Its population was all of the students in Grade VIII of State Junior Secondary Schools of Karanganyar. The samples of the research were taken by using the stratified cluster random sampling technique. The samples consisted of 284 students. The instruments used to gather the data were test of learning achievement in Mathematics and test of spatial ability. The proposed hypotheses of the research were tested by using the two-way analysis of variance with unbalanced cells. The results of the research were as follows. 1) the students instructed TAI with AfL had a better learning achievement in Mathematics than those instructed TAI and those instructed with the direct learning model. Furthermore, the students instructed with TAI had the same learning achievement in Mathematics as those instructed with the direct learning model. 2) The learning achievement in Mathematics of the students with the high spatial ability was better than that of the students with the moderate spatial ability and that of the students with the low spatial ability. In addition, the learning achievement in Mathematics of the students with the moderate spatial ability was better than that of the students with the low spatial ability. 3) In each learning model of the TAI with AfL, TAI, and the direct learning model, the students with the high spatial ability had a better learning achievement in Mathematics than those with the moderate spatial ability and those with the low spatial ability. Moreover, the students with the moderate spatial ability had a better learning achievement in Mathematicsthan those with the low spatial ability. 4) In each of the students with the high, moderate, and low spatial abilities, TAI with AfL results in a better learning achievement in Mathematics than TAI and the direct learning model. Furthermore, TAI results in the same learning achievement in Mathematics as the direct learning model.Keywords: Team Assisted Individualization (TAI), Assessment for Learning (AfL), and spatial ability